Diversifikasi Produk Kuliner Durian Desa Padabeunghar - Adestya Ayu Armielia; Yoanita Alexandra; Oqke Prawira Triutama (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
This community outreach was carried out in Padabeunghar Village, Kuningan because most of the population there still depends on forest and agricultural products for their income eventhough there are potential income from tourism and culinary businesses. This activity aims to train residents of Padabeunghar Village to make product diversification in specialty culinary that can become village identities and tourist attractions. The villagers were also given cooking utensils to support the entrepreneurial activities in the culinary field. Product diversification with Durian-based ingredients was chosen because durian is one of the main commodities in Padabeunghar Village. Padabeunghar durian is used as the main ingredient in the making of Durian Pie and Durian Pancakes. The training method is structured in several stages; (1) an initial survey to determine potential culinary products, (2) planning and testing recipes, (3) making standard recipes, (4) implementation, and (5) evaluation. The results of this activity are to help villagers to produce Padabeunghar specialty culinary products, increase product competitiveness (in terms of quality, quantity, added value, service, and product diversification), and introduce the application of multimedia technology to promote and sell products. Evaluation was carried out after the training, and the product diversification of Padabeunghar durians are marketed at food stalls in the tourist area of Padabeunghar Village.